2014
DOI: 10.1016/j.homp.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of inflammation response to murine cutaneous Leishmaniasis by homeopathic medicines: Antimonium crudum 30cH

Abstract: The treatment of mice with Antimonium crudum 30cH induced a predominantly B cell pattern of immune response in Leishmania (L.) amazonensis experimental infection, alongside the increase of free amastigote forms number in the infection site. The clinical significance of this study is discussed, further studies are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…20 Moreover, this correspondence was in accordance with in vivo effects of the same medicine. 21 Similar correlations have been described using ultra-high dilutions of Silicea terra and Phosphorus. 23,40,41 The studies described above have all been performed under highly controlled conditions, using milliliter volumes of liquids, as is usually the case in laboratory-based work.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…20 Moreover, this correspondence was in accordance with in vivo effects of the same medicine. 21 Similar correlations have been described using ultra-high dilutions of Silicea terra and Phosphorus. 23,40,41 The studies described above have all been performed under highly controlled conditions, using milliliter volumes of liquids, as is usually the case in laboratory-based work.…”
Section: Discussionsupporting
confidence: 61%
“…A previous study developed in our laboratory on the physicochemical properties of the drug Antimonium crudum 19,20 has shown that absorbance variations of solvatochromic dyes presented a clear relation with the biological effects of this drug in vitro and in vivo. 21,22 These findings suggest that solvatochromic dyes could be used as physico-chemical probes of biologically active high dilutions of different substances beyond Avogadro's number, based on dipole moment changes. 23 Discovering if solvatochromic dyes are sensitive enough to detect changes in the polarity of large water volumes would be a critical step in evaluating the plausibility of using high dilutions in many field situations, such as environmental management, 24 organic agriculture 25 and in herd, broiler, and fish breeding, with a view to improving productivity.…”
Section: Introductionmentioning
confidence: 97%
“…Infection of macrophages in-vitro can provide a sensitive translational model for understanding the effects of highly diluted substances on the immune response. This model was previously validated by the results obtained in Leishmania amazonensis-infected macrophages treated with various homeopathic protocols, [13][14][15] which are related closely to observations obtained in-vivo. Using various models of macrophage challenge with other micro-organisms, our team has previously shown that highly diluted medicines, instead of killing the micro-organisms, facilitate the organization of a more effective pattern of macrophage response and arrest the parasite's life cycle.…”
Section: Introductionsupporting
confidence: 61%
“…Using various models of macrophage challenge with other micro-organisms, our team has previously shown that highly diluted medicines, instead of killing the micro-organisms, facilitate the organization of a more effective pattern of macrophage response and arrest the parasite's life cycle. [8][9][10][13][14][15][16][17][18][19][20][21][22][23] For this reason, a similar model was designed herein to explain the clinical results, and avoiding new in-vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…16 In another study, Antimonium crudum 30c was found to inhibit the chronic inflammatory response in mice experimentally infected with CL and reduced the lesion size. 29 It was later identified that the clinical improvement was due to the reduction in certain cytokines, which had increased in response to the infection, and the blocking of chemokine CCL2 (MCP-1), known for monocyte recruitment and parasite multiplication. 30 Similarly, in the present investigation, the decrease in infection may be due to an improvement in the suppressed immune system caused by VL.…”
Section: Parasite Loadmentioning
confidence: 99%